The Relationship Between Nutrition Knowledge Level With Dementia Among Pre-Elderly In Sukomanunggal District, Surabaya - Adinda Diana Putri Ramdhani,; Salma Shafrina Aulia, (Jurnal Gizi dan Kesehatan Nusantara, 2025)
Dementia is a progressive clinical syndrome characterized by disturbances in several cognitive functions, such as loss of short-term and long-term memory, thinking, judging, orientation, calculation, and learning ability as well as personality changes, impaired abilities, and motor skills. This study aimed to analyze the relationship between nutritional knowledge with dementia among pre-elderly in Sukomanunggal District, Surabaya City. This study used a quantitative method with cross sectional approach. Purposive sampling technique used to determine respondent and it was obtained 70 pre-elderly respondents aged 45-59 years in Sukomanunggal District, Surabaya City was obtained. Data collection on nutritional knowledge used a nutritional knowledge test and dementia screening used the Mini Mental State Examination (MMSE) questionnaire. Data were analysed in this study using the spearman rank. The results showed that there was no significant relationship between nutritional knowledge with dementia in pre-elderly in Sukomanunggal District, Surabaya City (p-value = 0.155). It is hoped that the results of this research will help the public, especially the elderly, to be able to apply the information or knowledge they already know about nutrition to their daily lives.he results of this study are expected to encourage the public, especially pre-elderly people, to pay more attention to the diversity of food they consume, both in terms of quality, frequency, and type of food.